2017
DOI: 10.3892/ol.2017.5861
|View full text |Cite
|
Sign up to set email alerts
|

Jak3 is involved in CCR7-dependent migration and invasion in metastatic squamous cell carcinoma of the head and neck

Abstract: Abstract. Patients with cervical lymph node metastasis in squamous cell carcinoma of the head and neck (SCCHN) exhibit a poor prognosis and low 5-year survival rate. It has been proven that chemokine receptor 7 (CCR7) promotes cellular migration and invasion in metastatic SCCHN. In the present study, the metastatic SCCHN PCI-37B cell line was utilized to explore the role of Janus activated kinase-3 (Jak3) in the CCR7-mediated signaling pathway in metastatic SCCHN cells. It was observed that phospho-Jak3 was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Previous research reported that CCR7 regulate metastasis in head and neck SCC (28,33,34,35). The importance of the signaling way Janus activated kinase-3 (Jak3) in the metastasis of malignant head and neck tumors mediated by CCR7 and its ligands, can be a new target for treatment of these patients (36). Also, was reported that CCR7 can activate JAK2/STAT3 and to promote metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported that CCR7 regulate metastasis in head and neck SCC (28,33,34,35). The importance of the signaling way Janus activated kinase-3 (Jak3) in the metastasis of malignant head and neck tumors mediated by CCR7 and its ligands, can be a new target for treatment of these patients (36). Also, was reported that CCR7 can activate JAK2/STAT3 and to promote metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…CCR7 belong to the GPCR family and it is already known that activation of GPCRs can stimulate a number of intracellular signalling pathways. Indeed, binding of CCL19 or CCL21 to CCR7 is shown to result in activation of intracellular signalling pathways in tumour cell including PI3/akt [221][222][223], MAPK/ERK [161,[224][225][226][227], and Jak/STAT [228,229] pathways (Figure 1). Through modulation of these intracellular pathways, the CCR7 axis can exert a multifaceted influence on the biology of the cell and in particular have involvements in metastasis which goes J o u r n a l P r e -p r o o f beyond directing the migration.…”
Section: Wider Participation Of the Ccr7 Axis In Tumour Expansionmentioning
confidence: 99%
“… 49 Developing new therapeutics highly specific to either JAK1 or JAK3 could be greatly beneficial for patients with cancer and immune-related diseases, or even infections. Indeed, JAK1 and JAK3 have been widely described as potential therapeutic targets for several types of cancer, including gliomas, 50 , 51 head and neck cancers and oesophageal squamous cell carcinoma, 52 , 53 , 54 , 55 breast cancer, 56 , 57 multiple myeloma, 58 , 59 colon cancer 60 , 61 and pancreatic cancer, 62–64 as well as for developing cancer immunotherapies. 65 JAK3 has been particularly highlighted as a therapeutic target in immune cell-related cancers, including B-lineage acute lymphoblastic leukaemia 66 and natural killer/T-cell lymphoma, 67 and also for improving allotransplantation.…”
Section: Discussionmentioning
confidence: 99%